The Factors of Digitality and Sustainable Competitiveness in the Domestic Context - Béresné Mártha, Bernadett (International Journal of Engineering and Management Sciences, 2018)
The recovery of international relations and the development of technology are in correlation with the increasing globalization tendencies. These processes increase the interdependence of countries, but also the competition between them. The factors of competition are constantly changing and being revalued. As a result new elements appear in addition to the traditional elements, and there are assimetries between existing components. The economic performance of a country increasingly depends on the knowledge and technology, its economic success on the use of knowledge. The purpose of the study is to present and analyze the proxies that define and shape the role of Hungary by IMD Competitiveness Research Center and by the complex indicators developed by Korea-based SolAbility. It also draws attention to all the factors that will significantly effect our country's economy in the future.